CBD Suppression of EAE is Correlated with Early Inhibition of Splenic IFN-γ+CD8+ T Cells and Modest Inhibition of Neuroinflammation - Nichols, James M. (J Neuroimmune Pharmacol, 2020)
In this study cannabidiol (CBD) was administered orally to determine its effects and mechanisms in the experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis (MS). We hypothesized that 75mg/kg of oral CBD given for 5 days after initiation of disease would reduce EAE severity through suppression of either the early peripheral immune or late neuroimmune response. EAE was induced in C57BL/6 mice at two different magnitudes, and peripheral inflammatory and neuroinflammatory responses were measured at days 3, 10, and 18. Th1, Th17, Tc1, Tc17, Tregs, and myeloid derived suppressor cells (MDSC) were identified from the lymph nodes and spleens of each mouse to determine if CBD altered the suppressor cell or inflammatory cell populations in secondary lymphoid tissues. Additionally, neuroinflammation was identified in brain and spinal cord tissues using various immunohistochemical techniques and flow cytometry. Early treatment of EAE with oral CBD reduced clinical disease at the day 18 timepoint which correlated with a significant decrease in the percentage of MOG(35–55) specific IFN-γ producing CD8(+) T cells in the spleen at day 10. Analysis of both T cell infiltration and lesion size within the spinal cord also showed a moderate reduction in neuroinflammation within the central nervous system (CNS). These results provide evidence that oral CBD suppressed the peripheral immune response that precedes neuroinflammation; however, analysis of the neuroinflammatory endpoints also suggest that the modest reduction in neuroinflammation was only partially responsible for CBD’s neuroprotective capability.